Distiller’s grain market price relationships, discovery, and risk management - Van Winkle, T.W.; Schroeder, Ted C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The substantial increase in corn use by the ethanol refinery industry (Figure 1) has resulted in livestock producers, especially cattle feeders, substituting distiller’s grain (DG) for corn in feed rations. DG futures markets do not exist, but actively traded corn and soybean meal (SBM) futures are the most probable markets for hedging DG price risk. Therefore, the ability to offset DG price risk using corn and SBM futures is incorporated into analysis to quantify the strength of price relationships. If DG prices and corn or SBM futures prices are strongly related, then a viable cross hedging opportunity might exist. If they are not related, then cross hedging DG price risk in corn or SBM could increase risk. The growing importance of DG markets demonstrates a need for information regarding price relationships in the industry. The purpose of this study is to determine DG price relationships across locations and over time. Particular objectives include estimating how strongly related DG prices are across different locations, determining whether price leadership is present, and quantifying risk in cross hedging DG using existing futures contracts.
Keywords: Beef; Cattle; Distiller’s grain (DG); Soybean meal (SBM)